2020
DOI: 10.1017/s0031182020001262
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the diagnosis and treatment of neuroangiostrongyliasis: updated recommendations

Abstract: A subcommittee of the Hawaii Governor's Joint Task Force on Rat Lungworm Disease developed preliminary guidelines for the diagnosis and treatment of neuroangiostrongyliasis (NAS) in 2018 (Guidelines, 2018). This paper reviews the main points of those guidelines and provides updates in areas where our understanding of the disease has increased. The diagnosis of NAS is described, including confirmation of infection by real-time polymerase chain reaction (RTi-PCR) to detect parasite DNA in the central nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…In humans, early diagnosis of neuroangiostrongyliasis is di cult due to the range of symptoms and variation in incubation rates [9]. In the USA, although symptomatology and exposure history are considered, con rmed diagnosis is primarily via PCR using an ITS1-based assay (AcanITS1) for the detection of A. cantonensis DNA in the cerebrospinal uid (CSF) of humans [10,11,12]. Unfortunately for the patient, it takes time for the parasite to reach the CNS and thus become detectable by PCR [13], time during which neurological damage has likely already occurred.…”
Section: Introduction Methods and Resultsmentioning
confidence: 99%
“…In humans, early diagnosis of neuroangiostrongyliasis is di cult due to the range of symptoms and variation in incubation rates [9]. In the USA, although symptomatology and exposure history are considered, con rmed diagnosis is primarily via PCR using an ITS1-based assay (AcanITS1) for the detection of A. cantonensis DNA in the cerebrospinal uid (CSF) of humans [10,11,12]. Unfortunately for the patient, it takes time for the parasite to reach the CNS and thus become detectable by PCR [13], time during which neurological damage has likely already occurred.…”
Section: Introduction Methods and Resultsmentioning
confidence: 99%
“…Benzimidazoles are one of the few classes of anthelmintics that are effective against A. cantonensis [ 157 ], especially albendazole, which is currently the only available FDA-approved benzimidazole known to be capable of crossing the BBB [ 11 ]. An increasing number of guidelines recommend the use of albendazole–corticosteroid cotherapy for the management of neuroangiostrongyliasis, for example, the Sydney Children’s Hospital Network, Australia (2018) [ 158 ]; the Children’s Health Queensland Hospital and Health Services, Australia (2019) [ 159 ]; the Hilo Medical Center, Hawaii (2020) [ 160 ]; and the Hawaii Governor’s Joint Task Force on Rat Lungworm Disease Clinical Subcommittee [ 9 ]. Experimental studies have also demonstrated the in vitro efficacy of albendazole on A. cantonensis L3 [ 157 , 161 ].…”
Section: Discussionmentioning
confidence: 99%
“…Benzimidazole anthelmintics are known to bind to the colchicine-sensitive site of β-tubulin and hinder microtubule assembly, corrupting the cascade of cell division at metaphase, which ultimately leads to death of the parasite [ 8 ]. Currently, in the United States, specific treatment for neuroangiostrongyliasis is initiated only after diagnostic confirmation through the detection of A. cantonensis DNA in the cerebrospinal fluid (CSF) [ 9 ]. However, at this point of the disease, the larvae are likely to have induced neurological damage.…”
mentioning
confidence: 99%
“…There is currently no consensus on treatment of angiostrongyliasis though we are moving towards it [ 57 ]. Administering albendazole for 14 days was studied in only one randomized and placebo-controlled trial involving 71 subjects and cleared headaches more quickly [ 58 ].…”
Section: Discussionmentioning
confidence: 99%